2005
DOI: 10.1007/s00248-004-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Frankia Microsymbionts from the Relict Species Myrica faya (Ait.) and Myrica rivas-martinezii (S.) in Canary Islands and Hawaii

Abstract: In the Western Canary Islands, Myrica faya and Myrica rivas-martinezii (Myricaceae) are phylogenetically close, endemic, actinorhizal species presumed to be remnants either of the European or the African Tertiary floras. Unisolated Frankia strains from field-collected nodules on Tenerife, Gomera, and La Palma Islands were compared by their rrs gene and 16S-23S intergenic spacer (IGS) restriction patterns. To compare the genetic diversity of Frankia strains from within and outside the host's native range, nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…Other authors have reported a greater genetic diversity among Frankia strains symbiotic with Alnus, or with its host compatible genus Myrica, in several other geographical locations throughout the world Dai et al, 2004;Huguet et al, 2004b;Huguet et al, 2005;Oakley et al, 2004). Several reasons could account for the low diversity of Frankia strains detected in our study as compared with those reported in other works.…”
Section: Distribution Of Restriction Patternscontrasting
confidence: 78%
See 1 more Smart Citation
“…Other authors have reported a greater genetic diversity among Frankia strains symbiotic with Alnus, or with its host compatible genus Myrica, in several other geographical locations throughout the world Dai et al, 2004;Huguet et al, 2004b;Huguet et al, 2005;Oakley et al, 2004). Several reasons could account for the low diversity of Frankia strains detected in our study as compared with those reported in other works.…”
Section: Distribution Of Restriction Patternscontrasting
confidence: 78%
“…France and Belgium (Huguet et al, 2004b) or the Northeast and Midwest of the United States (Huguet et al, 2004a)] being there, therefore, the climatic conditions less restrictive to the adaptation of nodulating Frankia strains. On the other hand, it has been reported that close phylogenetically related Myrica species (M. faya and M. rivas-martinezii) growing sympatrically are nodulated by different Frankia strains, indicating that they have the capacity to select specific Frankia genotypes present in soil (Huguet et al, 2005). If the same occurs in the genus Alnus, the range of Frankia strains susceptible to be selected under natural conditions by a determined Alnus species (or even genotype) could vary broadly.…”
Section: Distribution Of Restriction Patternsmentioning
confidence: 94%
“…Our results agree with those of Moora et al (17) and Huguet et al (12), who found different arbuscular mycorrhizal fungi (AMF) and Frankia strains, respectively, in the roots of single pairs of rare and common congeners. Our work extends their conclusions because we replicated plant rarity and commonness by including more than two plant species, and we examined the whole rhizospheric bacterial community instead of exclusively plant-associated microbial mutualists.…”
supporting
confidence: 93%
“…Because of their unusual ability to effectively nodulate with strains from both clusters I and III, alternatively referred to as the Alnus-, and Elaeagnus-Host Infection Groups (HIGs), when inoculated under laboratory conditions, the genus Morella (a member of the Myricaceae, along with actinorhizal Myrica and Comptonia) is considered promiscuous (Vandenbosch and Torrey 1983;Torrey 1990;Maggia and Bousquet 1994;Huguet et al 2005). Although the symbiotic preferences of comparatively few Morella species have been studied under natural field conditions, host/endophyte associations have typically been found to be more specific than those found when hosts are greenhouse-grown, and it is thought that this may be a consequence of prevalent edaphic conditions.…”
Section: Introductionmentioning
confidence: 99%